Pengaruh Pemberian Probiotik EM4 dalam Pakan Komersial terhadap Pertumbuhan Benih Ikan Nila (Oreochromis Niloticus L) - Wulandari Rihhadatul Aisy; Nurul Hayati; Muhajir Muhajir; Angga Pratama Putra (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
This study aims to determine the effect of adding EM4 probiotics in various doses to commercial feed on the growth of jatimbulan tilapia (Oreochromis niloticus L). Probiotics are known to play a role in increasing digestive efficiency, nutrient absorption, and maintaining the health of the fish's digestive tract, so they are expected to support optimal growth. The research method used was a Completely Randomized Design (CRD) with four treatments, namely: P0 (control/without probiotics), P1 (5 ml EM4/kg feed), P2 (7 ml EM4/kg feed), and P3 (11 ml EM4/kg feed), each with four replications. The parameters observed were the growth in length and weight of jatimbulan tilapia during the maintenance period. The results showed that the administration of EM4 probiotics at certain doses was able to provide a significant effect on the growth of tilapia compared to the control treatment. Treatment P2 (7 ml/kg feed) provided the best growth results compared to other doses, both in terms of increasing length and body weight. Meanwhile, administering probiotic doses that are too low (P1) or too high (P3) tends to be less effective in supporting optimal growth. This is thought to be due to the disruption of the microbial balance in the digestive tract when the probiotic dosage is incorrect. This research provides useful information for Jatimbulan tilapia cultivation practices, particularly regarding the use of probiotics to increase growth efficiency. Using the correct probiotic dosage can be a strategy to increase the productivity and sustainability of freshwater fish farming.